Quantum correlations and quantum Fisher information of two qubits in the presence of the time-dependent coupling effect - Raffah, Bahaaudin; Abdel-Khalek, S.; Berrada, K.; Khalil, E.; Al-Hadeethi, Yas; Almalky, Nawal; Mohamed Ridza Wahiddin (Springer Heidelberg, 2024)
Indexed by Scopus